Respiratory Muscle Training Improves Exercise Performance and Quality of Life in Cancer Survivors: A Pilot Study. Issue 2 (April 2017) - Ray, Andrew D.; Williams, Brian T.; Mahoney, Martin C.
Abstract : Background: Respiratory muscle weakness represents one of the potential mechanisms contributing to exertional dyspnea and reduced exercise performance in lung and breast cancer survivors. Purpose/Objective: Pilot study of a respiratory muscle training (RMT) program to improve exercise capacity and quality of life (QOL) and reduce dyspnea in breast and lung cancer survivors. Methods: Participants performed 3 sets of 15 repetitions against spring-loaded inspiratory and expiratory valves, 3 days per week, for 4 weeks, with weekly increases in resistance. Maximal expiratory (MEP) and inspiratory pressures (MIP), exercise tests ( O2peak, submaximal cycling endurance at 70% of peak, and Six-Minute Walk Test [6MWT]) along with questionnaires (Baseline Dyspnea Index and SF-36 [36-Item Short Form Health Survey]) were completed pre- and post-RMT. Design: Single-arm pilot study. Setting: University research and academic medical center. Patients: Lung and breast cancer survivors with the presence of mild-to-moderate dyspnea symptoms not attributed to cardiopulmonary disease. Results: Post-RMT, MIP and MEP increased 29% ± 21% and 34% ± 32%, respectively ( P < .001). Submaximal endurance time (16.9 ± 7.4 minutes vs 31.4 ± 7.7 minutes, P = .001), the distance covered in the 6MWT (427 ± 84 m vs 471 ± 95 m, P = .005), dyspnea index (6.4 ± 1.0 vs 7.6 ± 1.3, P = .02), and QOL (total 85.3 ± 9.4 vs 97.8 ± 12.7, P = .014) were all significantly improved post-RMT. Limitations: Limited sample size and short duration of follow-up. Conclusions: These preliminary results support the continued investigation of a respiratory muscle-training program to improve respiratory muscle strength, exercise performance, and QOL, as well as to decrease dyspnea symptoms among cancer survivors.